Polaron Delocalization in Donor–Acceptor Polymers and its Impact on Organic Electrochemical Transistor Performance. Issue 14 (26th February 2021) - Moser, Maximilian; Savva, Achilleas; Thorley, Karl; Paulsen, Bryan D.; Hidalgo, Tania Cecilia; Ohayon, David; Chen, Hu; Giovannitti, Alexander; Marks, Adam; Gasparini, Nicola; Wadsworth, Andrew; Rivnay, Jonathan; et al.
Abstract: Donor–acceptor (D‐A) polymers are promising materials for organic electrochemical transistors (OECTs), as they minimize detrimental faradaic side‐reactions during OECT operation, yet their steady‐state OECT performance still lags far behind their all‐donor counterparts. We report three D‐A polymers based on the diketopyrrolopyrrole unit that afford OECT performances similar to those of all‐donor polymers, hence representing a significant improvement to the previously developed D‐A copolymers. In addition to improved OECT performance, DFT simulations of the polymers and their respective hole polarons also reveal a positive correlation between hole polaron delocalization and steady‐state OECT performance, providing new insights into the design of OECT materials. Importantly, we demonstrate how polaron delocalization can be tuned directly at the molecular level by selection of the building blocks comprising the polymers' conjugated backbone, thus paving the way for the development of even higher performing OECT polymers. Abstract : Monomer selection in organic mixed ionic–electronic conduction polymers is shown to directly impact their polaron delocalization and consequently their performance in (bio)electronic devices, thus outlining molecular design guidelines for the development of next generation high‐performance materials.